The THE INFLUENCE OF BRAND PERSONALITY AND SELF-CONCEPT ON BRAND ATTACHMENT OF APPLE PRODUCTS - Olivia Ulag; William J. F. A. Tumbuan; Lawren J. Rumokoy (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The aim of this study is to understand the impact of brand personality and self-concept on people’s brand attachment of Apple products, as for now Apple products are known to have many great qualities of products on their field. The population of this research is the people in Manado and the quantitative method is used in this research. In order to collect the data, questionnaires were distributed to 100 people in Manado. The result of this research shows that brand personality has positive relationship toward brand attachment with significant influence, and self-concept also has positive relationship toward brand attachment with significant influence   Keywords: brand personality, self-concept, brand attachment